Clinical laboratory testing for smoking toxicity: implications for early identification of respiratory diseases - Nwose, Ezekiel U.; Bwititi, Phillip T.; Richards, Ross S. (International Journal of Research in Medical Sciences, 2017)
Smoking toxicity has short and long term clinical effects and also leads to organ damage. However, clinical assessment in the context of early identification of smoke toxicity by evidence-base pathology is yet to be practiced. The present study was aimed to assess the knowledge and practice of health practitioners regarding clinical laboratory testing of smoking toxicity, with a view to generate a debate on why and how to test. In this pilot study, various health practitioners and students were asked via interviews about laboratory testing of smoking toxicity. There is considerable dismissal of ‘why’ to test and up 57% responded that it was unnecessary. However, there is general opinion that laboratory routine tests can be used to identify toxicity. It appears that there is a gap between knowledge and practice of clinical laboratory testing of cigarette toxicity. Students and health practitioners have the knowledge on smoke toxicity but this requires articulation into evidence-base pathology for early identification and intervention of subclinical pathology in smoking toxicity, especially before noticeable organ damage.